2020
DOI: 10.1101/2020.10.30.20222471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual Scoring of Chest CT at Hospital Admission Predicts Hospitalization Time and Intensive Care Admission in Covid-19

Abstract: Background The extent and character of lung involvement on chest computerized tomography (CT) have a prognostic value in covid-19 but there is lack of consensus on how to assess and stage CT features. A scoring system of lung involvement in covid-19, Örebro covid-19 Scale (ÖCoS) was implemented in clinical routine on April 1 2020 in Örebro Region, Sweden. The ÖCoS-severity score measures the extent of lung involvement while ÖCoS-temporal stage characterizes the parenchymal involvement. The objective of the pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Another study on baseline chest CT scans and clinical and laboratory data of 72 patients admitted with COVID-19 pneumonia showed lung severity score > was associated with a significantly lower recovery rate and discharge and extended hospitalization in patients admitted for COVID-19 pneumonia [ 29 ]. Similar to our findings, Ahlstrand et al previously reported that chest CT score at hospital admission correlates closely with hospital length of stay and ICU admission [ 30 ]. CT severity score combined with age and history of at least one underlying disease had 79.7% sensitivity and 65.5% specificity in predicting the adverse outcomes in a previous study [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Another study on baseline chest CT scans and clinical and laboratory data of 72 patients admitted with COVID-19 pneumonia showed lung severity score > was associated with a significantly lower recovery rate and discharge and extended hospitalization in patients admitted for COVID-19 pneumonia [ 29 ]. Similar to our findings, Ahlstrand et al previously reported that chest CT score at hospital admission correlates closely with hospital length of stay and ICU admission [ 30 ]. CT severity score combined with age and history of at least one underlying disease had 79.7% sensitivity and 65.5% specificity in predicting the adverse outcomes in a previous study [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…At study site 1 (Örebro) structured chest CT assessment of radiological lung involvement was part of the regional clinical routine in the evaluation of hypoxemic COVID-19 patients on hospital admission and was often repeated if patients deteriorated (22). Serum samples from hospitalized patients were collected on days 0 (day of enrollment), 2, and 4, and from non-hospitalized patients on day 0, and analyzed for eCIRP concentrations.…”
Section: Study Protocolmentioning
confidence: 99%
“…previously reported that chest CT score at hospital admission correlates closely with hospital length of stay and ICU admission (30). CT severity score combined with age and history of at least one underlying disease had 79.7% sensitivity and 65.5% speci city in predicting the adverse outcomes in a previous study (31).…”
Section: Chest Ct Predictors Of Unfavorable Outcomesmentioning
confidence: 73%